Fluorinated Strategies Among All‐Solid‐State Lithium Metal Batteries from Microperspective. Issue 1 (13th October 2022) - Yang, Fan; Liu, Yujing; Liu, Tiefeng; Wang, Yao; Nai, Jianwei; Lin, Zongxi; Xu, Hao; Duan, Dan; Yue, Ke; Tao, Xinyong
Abstract : All‐solid‐state lithium metal batteries (ASSLMBs) are becoming the crucial energy‐storage candidate in achieving both theoretical capacity and safety guarantee. However, the inherent defects of solid electrolytes (SEs) (low ionic conductivity, lack of mechanical properties, weak antioxidant capacity, etc.) and the existence of interfacial issues between electrodes (cathode/electrolyte interface and anode/electrolyte interface) hinder further practical application. To overcome these problems, many approaches have been developed, such as composite solid electrolytes, interfacial coatings, electrolyte additives, etc. Among them, fluorides and its derivatives with good chemical stability are generally believed as one of the significant materials for stabilizing ASSLMBs. In this article, the progress of fluorinated strategies in ASSLMBs is summarized from the aspects of fluorinated SEs and fluorinated interfaces. Meanwhile, the enhanced mechanisms of fluorinated strategies are emphasized from the microscopic view of the nanostructures evolution based on the discussion of emerging analysis technologies such as cryogenic transmission electron microscopy. The progress of future fluorinated strategies is prospected, and this review may thus instruct the rational design of high performance ASSLMBs. Abstract : Herein, the design concept and the corresponding function mechanisms of fluorinated strategies in solid‐state lithium metal batteries from two aspects, fluorinated solid electrolytes and fluorinated interfaces, are discussed. Meanwhile, the enhanced mechanisms of fluorinated strategies are emphasized from the microscopic view of nanostructures evolution based on the discussion of emerging analysis technology.